"Caring for the Uncared for": A Novel Initiative of Madras Medical College - Theranirajan Ethirajan; Priya Senthilkumar; Usha Gnanasambandam; Susan Jacob; Gopalakrishnan Natarajan; Karthick Rajendran (SAGE Publishing, 2023)
Background: Every society has persons with illness who do not have any family support. Taking care of such uncared-for patients requires a well-structured system providing medical, psychological, emotional, and rehabilitory support. The first ever rehabilitation ward among government hospitals in Tamil Nadu was created at Rajiv Gandhi Government General Hospital (RGGGH), Chennai with the motto of "Caring for the uncared for." This paper highlights the organizational structure, functionality, profile of patients admitted, challenges faced, and the outcome of patients admitted in the rehabilitation ward. Methods: A retrospective study was done on the "untended" patients, who were admitted in the rehabilitation ward at Rajiv Gandhi Government General Hospital (RGGGH), Chennai, Tamil Nadu, India from December 2020 to June 2022. Sociodemographic and clinical characteristics and outcome of the patients were analyzed. Results: A total of 201 adults with physical disabilities or mixed physical and psychiatric disabilities were admitted for intensive rehabilitation. Common medical illnesses included orthopedic disorders in 80 (39.8%), followed by neurological illness in 43 (21.4%) patients. The median length of stay was 50 (24.5-103.5) days with longest stay of 447 days. Of those patients who recovered, 54 patients (26.9%) reunited with family and returned home and 125 (62.2%) patients were sent to old age homes/asylums. Conclusion: A dedicated ward for untended patients is the first of its kind in the state of Tamil Nadu, India. Such a venture has proved to be of benefit, considering the positive outcome in a significant proportion of the beneficiaries.